Perancangan Sistem Pendukung Keputusan Pemilihan Peserta LKS Dengan Kombinasi Metode Gain Ratio Dan Moora - Agung Saputro; Vihi Atina; Rudi Susanto (Infotek: Jurnal Informatika dan Teknologi, 2023)
At SMK Negeri 1 Kismantoro, before this system was used, it used to only use manual or subjective methods, meaning that teachers still chose students directly. The selection of outstanding students must really be used as a reference for the following year to ensure increased academic success. This competition is held every year. SMK Negeri 1 Kismantoro sends a team every year to advance in this competition. Decision support systems can be made using several methods, one of which is the Moora and Gain Ratio method. This support system can assist in making decisions in selecting outstanding students for the SMK Negeri 1 Kismantoro competition. Operation of the Moore method consists of giving weight to each criterion. The Increment Ratio method is carried out to find the criteria used in the moora method, namely with the highest value having 4 of the highest, namely the card criteria is directly proportional to the gain of (0.44644), practice with a gain of (0.88129), attitude (personality) with the advantage (0.44644), skills with advantage (0.42836). The Moora method can choose alternatives and rank them to make the best student recommendations based on predetermined criteria where the Lutfiyatul Rosida alternative (A10) is the student with the best performance with Yi-Max = 0.165.